Is Microfinance Truly Driving Entrepreneurship? Evaluating the Financial Impact of MFIs in Pakistan (Journal of Social Sciences Review, 2025)
Microfinance has become an essential instrument for fostering financial inclusion and supporting entrepreneurial activity in developing economies, particularly where traditional banking services remain inaccessible to the majority. In Pakistan, microfinance institutions (MFIs) have increasingly provided enterprise loans aimed at improving livelihoods, encouraging self-employment, and stimulating small-scale business growth. While existing literature affirms the general benefits of microfinance, there remains a need to evaluate its financial impact on entrepreneurship development within the local context. This study focuses on Microfinance as the independent variable, examining its effect on three dependent variables: Asset Increase, Household Income, and Enterprise Performance. Data were collected from 381 borrowers of enterprise loans from three leading MFIs in Pakistan—Khushhali Microfinance Bank ltd, HBL Microfinance Bank ltd, and Advans Pakistan Microfinance Bank ltd. A quantitative research approach was adopted, and a structured questionnaire was administered, and the data were analyzed using SmartPLS 4 software through Partial Least Squares Structural Equation Modelling (PLS-SEM), which enables robust analysis of complex relationships between latent variables. The results indicate that microfinance has a statistically significant and positive impact on all three variables, suggesting that access to enterprise loans enhances the financial performance of micro-entrepreneurs. Each hypothesis tested was supported, reinforcing the role of microfinance as a catalyst for sustainable entrepreneurship development. These findings carry important implications for MFIs, policymakers, and development practitioners, offering a more nuanced understanding of how microfinance can be strategically leveraged to promote inclusive entrepreneurship development in Pakistan.
Keywords: Microfinance; Entrepreneurship Development; Financial Impact; Household Income; Asset Increase; Enterprise Performance